2007
DOI: 10.1094/phyto-97-12-1532
|View full text |Cite
|
Sign up to set email alerts
|

Topography and Crop Management Are Key Factors for the Development of American Leaf Spot Epidemics on Coffee in Costa Rica

Abstract: We monitored the development of American leaf spot of coffee, a disease caused by the gemmiferous fungus Mycena citricolor, in 57 plots in Costa Rica for 1 or 2 years in order to gain a clearer understanding of conditions conducive to the disease and improve its control. During the investigation, characteristics of the coffee trees, crop management, and the environment were recorded. For the analyses, we used partial least-squares regression via the spline functions (PLSS), which is a nonlinear extension to pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 29 publications
0
38
0
7
Order By: Relevance
“…The intensity of attacks by pests and diseases in these systems varies with the pest and its ecological requirements (Schroth et al 2000). In coffee (Coffea arabica), shade has been reported to favour Mycena citricolor in Costa Rica (Avelino et al 2007) (Figs. 15 and 16) but to hamper Colletotrichum kahawae in Cameroon (Mouen Bedimo et al 2008) due to changes in microclimate.…”
Section: Instances Where Psd Negatively Affects Natural Enemy Populatmentioning
confidence: 99%
“…The intensity of attacks by pests and diseases in these systems varies with the pest and its ecological requirements (Schroth et al 2000). In coffee (Coffea arabica), shade has been reported to favour Mycena citricolor in Costa Rica (Avelino et al 2007) (Figs. 15 and 16) but to hamper Colletotrichum kahawae in Cameroon (Mouen Bedimo et al 2008) due to changes in microclimate.…”
Section: Instances Where Psd Negatively Affects Natural Enemy Populatmentioning
confidence: 99%
“…It is demonstrated that advantages of associated shade trees are very important for coffee production in poor soils and under sub-optimal ecological conditions (Muschler and Bonnemann 1997; while their effects under optimal conditions remain controversial. On top of reducing coffee flowering intensity and hence yield, shade can result in a very humid micro-environment conducive to higher incidence of fungal diseases such as leaf rust (Hemileia vastatrix) and American leaf spot (Mycena citricolor), especially at high altitude and cloudy conditions (Avelino et al 2006(Avelino et al , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…The methodological approach chosen was a survey which is a proper method to study epidemics affected by a large number of cropping factors (Avelino et al. ). This method has been used to investigate disease epidemics in soya bean in the north‐central United States (Mila et al.…”
Section: Methodsmentioning
confidence: 99%